2012
DOI: 10.1111/j.1464-5491.2011.03471.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of arterial stiffness in women with gestational diabetes

Abstract: Although gestational diabetes may be a risk factor for development of cardiovascular disease, women with gestational diabetes do not have higher aortic stiffness than healthy pregnant women. Time of exposure to hyperglycaemia may have been insufficient to increase central arterial stiffness in women with gestational diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
2
11
1
Order By: Relevance
“…Endothelial dysfunction has been associated with a higher risk for cardiovascular disease in patients with diabetes, showing that the hyperglycaemic environment promotes micro-and macrovascular dysfunction [7,8]. Although GDM is considered a temporary state as it is alleviated by delivery, some studies have suggested that alterations in endothelial responsiveness occur [9], whereas others have suggested that the duration of exposure to hyperglycaemia is insufficient to induce vascular dysfunction [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial dysfunction has been associated with a higher risk for cardiovascular disease in patients with diabetes, showing that the hyperglycaemic environment promotes micro-and macrovascular dysfunction [7,8]. Although GDM is considered a temporary state as it is alleviated by delivery, some studies have suggested that alterations in endothelial responsiveness occur [9], whereas others have suggested that the duration of exposure to hyperglycaemia is insufficient to induce vascular dysfunction [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, all aortic stiffness parameters (aortic stiffness index, distensibility, and aortic strain) exhibited significant differences in the GDM patient group compared to the control group. There are very few studies in the literature addressing this topic (18,19), and none is revealing any statistical significance between these two groups. Secondly, a significant improvement was observed in aortic stiffness in normoglycemic postpartum GDM group, but there was no significant difference in hyperglycemic group.…”
Section: Discussionmentioning
confidence: 91%
“…Blood pressure is the best-known determinant of arterial stiffness, which might affect the results in the GDM group. Bulzico et al (18) did not find any significant difference in arterial stiffness between the GDM and control groups in a study conducted on a more homogeneous control group. They argued that time of exposure to hyperglycemia might be more important for arterial stiffness.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…37 Contrary to this results, Bulzico et al and Salmi et al, investigating arterial stiffness in gestational diabetes, found that their pregnant diabetic women, do not have significant increased arterial stiffness. 38,39 But in their study, patients with any previous glucose impairment were excluded. In other words, their study population was exposed to hyperglycemia only during their present pregnancy contrary to our pregnant diabetic women whose majority of them have history of gestational diabetes in previous pregnancies.…”
Section: Discussionmentioning
confidence: 99%